PEMBANGUNAN MANUSIA UNTUK MEWUJUDKAN MASYARAKAT KALIMANTAN TIMUR BERKUALITAS - to, Surip (Jurnal Borneo Administrator, 2011)
East Kalimantan is one of the provinces in Indonesia with the best Human Development Index. This is indicated by achieving fifth rank nationally for the last four years. It is certainly very interesting to find out various things in human development in East Kalimantan by the achievement it has. This study aims to measure the level of efficiency and quality of human development in East Kalimantan. The evaluation method used in this study is literature study. The evaluation uses two approaches namely the evaluation of the series and evaluation of given years. The tools used in data analyzing is Data Envelopment Analysis (DEA) DEA-Solver model LV3.0/CCR (CCR-O) / (CCR-I) and DEA- Solver LV3.0 / Window (Window-OC). The result of the analysis from both models shows that human development has been streamlined.Keywords: East Kalimantan, Education, Health, Economy, GDP, Evaluation.Kalimantan Timur  (Kaltim) merupakan salah satu provinsi di Indonesia dengan Index Pembangunan Manusia terbaik.  Hal tersebut ditunjukan dengan peringkat  5 nasional selama 4 tahun terakhir. Dengan prestasi tersebut tentunya sangat menarik untuk mengetahui berbagai hal dalam pembangunan manusia di Kaltim. Study ini bertujuan mengukur tingkat efisiensi dan kualitas pembangunanan manusia Kaltim. Selanjuntya, metode yang digunakan adalah evaluasi dengan study kepustakaan. Dalam melakukan evaluasi menggunakan dua pendekatan yakni evaluasi tahun seri dan evaluasi tahun tertentu. Alat bantu analisis yang digunakan  Data Envelopment Analysis (DEA) dengan model  DEA- Solver LV3.0/CCR (CCR-O)/(CCR-I) dan DEA-Solver LV3.0/ Window(Window-O-C). Hasil analisis kedua model tersebut menunjukan pembangunan manusia telah efisien. Kata Kunci : Kaltim, Pendidikan, Kesehatan, Ekonomi, PDRB, Evaluasi.